Late gadolinium enhancement does occur in Tako-tsubo cardiomyopathy — A quantitative cardiac magnetic resonance and speckle tracking strain study. (September 2016) - Gaikwad, Niranjan; Butler, Thomas; Maxwell, Ryan; Shaw, Elizabeth; Strugnell, Wendy E.; Chan, Jonathan; Figtree, Gemma A.; Slaughter, Richard E.; Hamilton-Craig, Christian
Abstract: Background: Late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMR) has been recommended to distinguish Tako-tsubo cardiomyopathy (TTC) from either acute myocardial infarction or myocarditis. Method: 44 consecutive patients with confirmed Mayo Clinic criteria for TTC underwent CMR imaging at 1.5 Tesla during the acute phase. 10 patients who had CMRI to exclude scar related ventricular tachycardia, and had negative studies, were used as negative controls. LGE was quantitated at two signal intensity thresholds (CircleCVi software) at > 2 and > 5 standard-deviations (SD) above reference myocardium, and compared to biomarkers. Findings: Mean door-to-CMR time was 57 hours. 18 patients (41%) had LGE > 2 SD localized to the area of abnormal wall motion, representing 28.9 ± 11.2% LV mass. In 16 of these 18 patients (89%) LGE signal intensity was > 5 SD above normal myocardium, representing 12.1 ± 10% LV mass. LGE signal intensity was significantly greater in TTC than in matched controls (p < 0.05) but lower than in STEMI patients (p < 0.05). Mean troponin was significantly higher in LGE positive patients (2.5 ± 1.8 vs 4.4 ± 6.9, p = 0.001). Mean ejection fraction (EF) by CMR was 45% ± 8.7 in LGE-negative, and 40% ± 7.1 in LGE-positive patients (p = 0.37). Recovery of segmental function was confirmed at follow-up, mean EF was 59% in both groups. Conclusion: LGE was present in 41% of cases of TTC, 89% of which had intense enhancement > 5 SD above normal myocardium. Presence of LGE was associated with worse myocardial injury in the acute setting, with no difference in recovery of function.